2021
DOI: 10.1177/1528083720987206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twist level on the mechanical performance of S-glass yarns and non-crimp cross-ply composites

Abstract: High modulus/high strength continuous fibres are used extensively for manufacturing textile preforms, as a reinforcement, for composites due to their excellent specific properties. However, their brittle behaviour and tendency to separate easily into individual filaments or bundles can lead to damages during manufacturing processes such as weaving and braiding. Thus, the critical step in the development of an optimal yarn for textile-reinforced composites is to find an optimum twist, which results in a minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The extension increased CT lateral pressure and compaction and, as a result, CT became denser and more coherent to strain. CT has a slightly loose twisting orientation that allows CMC + CA to penetrate and coat individual fiber surfaces, which further improves CT load bearing capacity by intercepting higher loads, thus leading to the improvement of elongation and avoiding early breakage [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extension increased CT lateral pressure and compaction and, as a result, CT became denser and more coherent to strain. CT has a slightly loose twisting orientation that allows CMC + CA to penetrate and coat individual fiber surfaces, which further improves CT load bearing capacity by intercepting higher loads, thus leading to the improvement of elongation and avoiding early breakage [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The long length of filaments enables low twist levels to maintain the components together . Thus, theoretical studies have shown that the tensile strength of filament yarns was the maximum when they were untwisted and decreased with the twist level. This behavior was experimentally shown by Yoshida et al using ramie-twisted yarns and by Dalfi et al, who demonstrated the maximum strength of S-glass yarns at a low twist level (30 twists per meter (tpm)). Discrepancies in this behavior have been observed in other studies, where the tensile strength of the yarns reached a maximum at higher twist levels.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, spinning composite technology has been used to compensate for the disadvantages of staple fibers and basalt fiber together. Unfortunately, problems of large modulus differences between staple fibers and basalt fiber exist, with high-modulus basalt fiber filaments breaking easily under high twist conditions (Kim et al, 2009;Li et al, 2018), while low-modulus staple fibers not cohesive yarns well in untwisted conditions (Qian et al, 2021;Dalfi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%